2007
DOI: 10.1021/es062121q
|View full text |Cite
|
Sign up to set email alerts
|

XAS and XPS Characterization of Mercury Binding on Brominated Activated Carbon

Abstract: Brominated powdered activated carbon sorbents have been shown to be quite effective for mercury capture when injected into the flue gas duct at coal-fired power plants and are especially useful when burning Western low-chlorine subbituminous coals. X-ray absorption spectroscopy (XAS) and X-ray photoelectron spectroscopy (XPS) have been used to determine information about the speciation and binding of mercury on two commercially available brominated activated carbons. The results are compared with similar analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
131
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(150 citation statements)
references
References 19 publications
18
131
1
Order By: Relevance
“…Similar XPS studies were also performed on lignite AC by Laumb et al 14 and on brominated AC by Hutson et al 12 to understand the effect of flue gas components on the sorbent surface chemistry. Via combination of observations from bench-scale tests and XPS studies, it appears that the presence of both SO 2 and NO x in the flue gas mixture leads to rapid breakthrough of Hg, indicating poor Hg capture.…”
Section: ■ Introductionmentioning
confidence: 79%
“…Similar XPS studies were also performed on lignite AC by Laumb et al 14 and on brominated AC by Hutson et al 12 to understand the effect of flue gas components on the sorbent surface chemistry. Via combination of observations from bench-scale tests and XPS studies, it appears that the presence of both SO 2 and NO x in the flue gas mixture leads to rapid breakthrough of Hg, indicating poor Hg capture.…”
Section: ■ Introductionmentioning
confidence: 79%
“…This is why the baseline-untested data in Figures 2a-2d each differ from one another. Table 1 provides a summary of the XPS Hg and Br binding energies for Hg-Br reference compounds available in the literature 27 and for the Hg-containing brominated AC sorbent investigated in the work presented here compared with the study carried out by Hutson et al 14 The reference data for the Hg 4f 7/2 binding energy of HgBr 2 indicate that this is the primary form of oxidized Hg on the surface; however, reference data are not available for the Hg 4f 5/2 binding energy for this compound. Additionally, reference data are not available for a potentially surface-bound species of HgBr with an oxidation state of ϩ1.…”
Section: Resultsmentioning
confidence: 99%
“…The XAFS spectra provided strong indication of Hg chemisorption on C. Their data suggest that the adsorption process occurs through a combination of halide, sulfide, and oxygen anions (either C-bound or C-sulfate-bound) present on the C surface. Additionally, Hutson et al 14 characterized chlorinated and brominated AC using X-ray absorption spectroscopy and X-ray photoelectron spectroscopy (XPS) after exposing the carbons to simulated flue gas containing Hg 0 (204 g/m 3 ; 24 parts per billion by volume [ppbv]). They found no Hg 0 on the AC surface, but they found adsorbed Hg-bromine (Br) and Hg-chlorine (Cl) complexes and propose that Hg capture by chlorinated and brominated carbons is achieved by surface oxidation of Hg 0 with subsequent adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…There is great interest in sorbent-based capture of elemental mercury [6][7][8][9][10][11][12][13] with application to spill scenarios, remediation technologies, respirator cartridges, incineration systems, and coal-fired combustion and gasification power plants. Many chemical formulations have been used or evaluated as mercury vapor sorbents, but the most common are based on activated carbon materials, which are widely used as sorbents for vapor-phase capture of elemental mercury due to low cost and flexible surface chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…al. [13] have shown that halogenation likely increases the capacity of activated carbons by providing active sites at which vapor phase elemental mercury is oxidized and then bound [13,14]. Another technique for increasing the mercury capture capacity of activated carbon is treatment with hydrogen sulfide, which was shown to increase the mercury capture capacity of activated carbon fiber by over 30 times even while destroying 95% of the BET surface area [15].…”
Section: Introductionmentioning
confidence: 99%